Risk of infections and mortality in Danish patients with cancer diagnosed with bone metastases: a population-based cohort study - Henrik Toft Sørensen; Thomas Bøjer Rasmussen; Andrea Marongiu; Niels Obel; Thomas Johannesson Hjelholt; Anouchka Seesaghur; Rohini K Hernandez; A B Pedersen (BMJ Open)
Objectives Risk of infections in patients with solid cancers and bone metastases (BM) and the subsequent impact on prognosis is unclear. We examined the risk of infections among patients with cancer diagnosed with BM and the subsequent impact of infections on mortality.Design Population-based cohort study.Setting Danish medical databases holding information on all hospital contacts in Denmark.Participants Adult patients with solid cancers and BM between 1 January 1994 and 30 November 2013.Outcome measures In the risk analyses, the outcome was time to hospitalisation for common severe infections, pneumonia, sepsis and urinary tract infections. In the mortality analysis, we used Cox regression to compute HRs of death, modelling infection as time-varying exposure, stratifying for primary cancer type and adjusting for age, sex and comorbidities.Results Among 23 336 patients with cancer and BM, cumulative incidences of common severe infections were 4.6%, 14.0% and 20.0% during 1 month, 1 year and 10 years follow-up. The highest incidence was observed for pneumonia, followed by urinary tract infections and sepsis. Infection was a strong predictor of 1 month mortality (adjusted HR: 2.1 (95% CI 1.8 to 2.3)) and HRs increased after 1 and 10 years: 2.4 (95% CI 2.3 to 2.6) and 2.4 (95% CI 2.4 to 2.6). Sepsis and pneumonia were the strongest predictors of death. Results were consistent across cancer types.Conclusion Patients with cancer and BM were at high risk of infections, which was associated with a more than twofold increased risk of death for up to 10 years of follow-up. The findings underscore the importance of preventing infections in patients with cancer and BM.